Corrosion Behavior of Anodic Self-Ordered Porous Oxide Layers on Stainless Steel - Prado, Lucia; Anastasiou, Evangelia; Virtanen, Sannakaisa (Journal of The Electrochemical Society, 2021)
In the present study we performed anodization of stainless steel AISI 316L varying the voltage, time and H2O concentration in the electrolyte obtaining self-ordered porous oxides. Open-circuit potential measurements, potentiodynamic polarization and electrochemical impedance spectroscopy were performed in 0.1 M H2SO4, 0.1 M NaCl and 0.1 M NaOH electrolytes. The metallic substrate underneath the grown oxide was also characterized. The results indicate that the corrosion behavior of the metallic substrate is not impaired by the anodization treatments. However, "crevice-induced intergranular corrosion" between the oxide and the metallic substrate was revealed after electrochemical measurements in the acidic electrolyte.
CRIS-Team WoS Importer:2021-03-05

Corrosion behavior of a slippery liquid infused porous surface on anodized stainless steel - Prado, Lucia; Anastasiou, Evangelia; Virtanen, Sannakaisa (Materials Letters, 2021)
In this work we present fabrication of slippery liquid infused porous surface (SLIPS) for anodized stainless steel AISI 316L. First, a porous sponge-like oxide layer was grown that subsequently was functionalized with perfluorinated molecules and finally infused with fluorinated Krytox oil. Morphology, composition analysis and wettability (also after corrosion testing) were characterized. Furthermore, corrosion behavior was studied with potentiodynamic polarization curves in 0.1 M H2SO4 and 0.1 M NaCl electrolytes. Our results demonstrate that the SLIPS coating protects the underlying material from corrosion, and the self-healing properties of the oil layer allow to recover localized damage during corrosion experiments.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Corrosion; Porous oxide; SLIPS; Stainless steel; Superhydrophobic; Wetting